Vertical and horizontal distribution of sand-dwelling dinoflagellates from Dinawan Island, Sabah, Malaysia - Mohammad Noor, Normawaty; Adam, Aimimuliani; Al-Has, Asilah; Saad, Shahbudin; Ahmad, Zuhairi (2016)
A study on the vertical and horizontal distribution of sand-dwelling dinoflagellates was conducted over a one year period in the coastal and lagoon areas of Dinawan Island. Fifty metre line transects were horizontally laid out perpendicular to the beach. At each station, 12–14 cm of sediments was vertically collected (10m interval). These sediments were divided every 2 cm over a 10 cm distance. At each slice of the sediments, sand-dwelling dinoflagellates were identified and counted. Furthermore, the sediments were sieved for sand size characteristics. Sand total phosphorus and total nitrogen were horizontally determined. Sixteen species of dinoflagellates were identified including five dominant dinoflagellates species viz. Prorocentrum lima, P. rhathymum, Amphidinium carterae, Bsymatrum caponii and Peridinium quinquercorne. The number of dinoflagellate cells was concentrated at the top 2 cm of the sediment and tended to decrease towards the deeper depth at the coastal and lagoon areas . The horizontal distribution of sand-dwelling dinoflagellates depended on the geomorphology of the area. In the coastal areas, the distribution of sand-dwelling organisms increased towards the sea but not towards the lagoon areas. However, a positive correlation was found between fine sediment size and sand dwelling abundance and not for other parameters studied. This indicates that the sediment characteristics played an important role in determining the abundance of sand-dwelling dinoflagellates.